ANALISIS KUALITAS SOAL BUATAN GURU DI SMP NEGERI 9 SATAP LANGOWAN PADA MATA PELAJARAN MATEMATIKA - Josua Titanio Manarisip; Rosiah Juliati Pulukadang; Nicky Kurnia Tumalun (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to describe the quality of questions made by teachers at SMP Negeri 9 Satap Langowan in mathematics, in terms of validity, reliability, level of difficulty, distinguishing power and distractors of the questions. This research method is a type of descriptive research with a quantitative approach. The research data is collected by interview and taking the students answer paper. The research data is processed by using SPSS (Statistical Package for Social Science) for windows version 22 and the Microsoft Excel 2013 program. The results showed that in class VII: 40% valid test; reliability test results at 0.972; difficulty level of 20% easy, 50% medium, and 30% difficult; discriminating power of 50% is bad, 40% is enough, and 10% is good; and there are 2 distractor items not working. Whereas in class VIII: 70% valid: reliability test results at 0.979; difficulty level of 10% easy, 70% medium, and 20% difficult; discriminating power of 20% poor, 20% fair, 40% good, 10% very good, and 10% negative; and there are 5 distractor items not working. The results showed that for class VII the quality of the questions was categorized as good in terms of reliability and distractors, while class VIII was categorized as good in terms of validity, reliability, level of difficulty, discriminating power, and distractor